2006
DOI: 10.1016/j.virol.2006.03.037
|View full text |Cite
|
Sign up to set email alerts
|

KSHV encoded LANA upregulates Pim-1 and is a substrate for its kinase activity

Abstract: Pim kinases are proto-oncogenes that are upregulated in a number of B cell cancers, including Epstein-Barr Virus (EBV) associated Burkitt's lymphoma. They have also been shown to be upregulated in Kaposi sarcoma-associated herpes virus (KSHV) infected primary B cells. Most cells in KSHV-associated tumors are latently infected and express only a small subset of viral genes, with KSHV latency associated nuclear antigen (LANA) being constitutively expressed. LANA regulates the transcription of a large number of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 63 publications
2
44
1
Order By: Relevance
“…In addition, Lu et al reported that Orf50 transcription is specifically repressed by KSHV LANA during viral latency (52). In dually infected PELs, K-LANA has been shown to suppress EBV genes by regulating the mSin3 corepressor complex (43), although K-LANA was also reported to activate EBV or human immunodeficiency virus genes (30,34), as well as cellular genes (4,40,83). The transcriptional activation and repression activities have been mapped to the amino and carboxyl termini of K-LANA, respectively (61,75,86).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Lu et al reported that Orf50 transcription is specifically repressed by KSHV LANA during viral latency (52). In dually infected PELs, K-LANA has been shown to suppress EBV genes by regulating the mSin3 corepressor complex (43), although K-LANA was also reported to activate EBV or human immunodeficiency virus genes (30,34), as well as cellular genes (4,40,83). The transcriptional activation and repression activities have been mapped to the amino and carboxyl termini of K-LANA, respectively (61,75,86).…”
Section: Discussionmentioning
confidence: 99%
“…LANA has been shown to be a substrate of PIM1 that phosphorylates LANA within the N-terminal domain. 84 In addition, a kinome wide expression library study identified activation of PIM1/PIM3 as a critical element for reactivation of a latent KSHV infection. 85 B-cell non-Hodgkin's lymphoma (NHLs) is characterized by chromosomal translocations leading to deregulation of several proto-oncogenes controlled by the immunoglobulin gene promoter and enhancer elements.…”
Section: Pim Serine/threonine Kinases In Hematologic Malignancies Andmentioning
confidence: 99%
“…Overexpression of Pim-2 reduces Ī³H2AX accumulation in DNA-damaged cells for exerting the protective effect. In the context of KSHV infection, the latent protein LANA is shown to activate Pim-1 and also act as a Pim-1 substrate (Bajaj et al, 2006), and the inactivation of LANA phosphorylation at Serine residues 205 and 206 by Pim-1 and Pim-3 kinases is required to trigger induction of KSHV lytic replication . Upon EBV latent infection, not only Pim-1 is required for LMP1-induced cell survival, but both Pim-1 and Pim-2 are also upregulated, and in turn enhance the activity of EBNA2 in driving EBVinduced cell immortalization (Rainio et al, 2005;Kim et al, 2010).…”
Section: Phosphorylation-mediated Viral Manipulation Of Dna Damage Rementioning
confidence: 99%